OpenUP extension for development of wireless sensor network applications. - Gian Ricardo Berkenbrock (2010)
This work presents an extension for OpenUP software development process, which includes the disciplines of Simulation and Prototyping for developing WSN applications. The simulation discipline was created to address performance, scalability, and integration requirements in the software development process for WSN application. The prototyping discipline was created in order to improve the knowledge about the system as well as to refine information about the system gathered from simulation study. We also describe the integration of both disciplines with OpenUP based on work products. A WSN application was developed in order to illustrate the use of the proposed disciplines. The WSN application monitors the environmental conditions required to age a sugar cane spirits. During the execution, the effort and time required to perform each activity is measured. We also performed a simulation study to investigate how proposed disciplines influence the software development process. A simulator based on discrete simulation approach is described and some experiments are performed, generating valuable results. Experiments with different team sizes and process models are performed and described. And their results are illustrated.